2021
DOI: 10.3390/v13010099
|View full text |Cite
|
Sign up to set email alerts
|

Canine Distemper Outbreaks in Wild Carnivores in Northern Italy

Abstract: Canine distemper (CD) is a fatal, highly contagious disease of wild and domestic carnivores. In the Alpine territory, several outbreaks have occurred in the past few decades within wild populations. This study investigated the presence of canine distemper virus (CDV) infections in wild carnivores in Lombardy, relating to the different circulating genotypes. From 2018 to 2020, foxes, badgers, and martens collected during passive surveillance were subjected to necropsy and histological examination, showing class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 23 publications
1
21
0
1
Order By: Relevance
“…From a nature conservation point of view, it is of paramount importance to learn more about diseases in animal species susceptible to CDV infection and prepare or ait mitigation efforts during epizootic events. Foxes' social behavior during the reproductive season and the dispersion of juvenile animals can played a major role in epizootic CDV ampli cation and diffusion in a wide geographic range, as discussed before 13,19 . CDV is known to easily cross species barriers and is able to infect different animal species.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…From a nature conservation point of view, it is of paramount importance to learn more about diseases in animal species susceptible to CDV infection and prepare or ait mitigation efforts during epizootic events. Foxes' social behavior during the reproductive season and the dispersion of juvenile animals can played a major role in epizootic CDV ampli cation and diffusion in a wide geographic range, as discussed before 13,19 . CDV is known to easily cross species barriers and is able to infect different animal species.…”
Section: Discussionmentioning
confidence: 97%
“…In Denmark, a major outbreak of canine distemper virus was detected in farmed minks (Neovison vison) from mink farms and a high number of species such as foxes, raccoon dogs (Nyctereutes procyonoides), and wild ferret (Mustela putorius), between 2012 and 2013 16 . The Europe lineage of CDV in wildlife has continued to be reported from nearby countries, rst in Italy from wild species, mainly foxes and badgers, between 2006 and 2009 17 , thereafter in Germany from raccoons (Procyon lotor) from 2015 and fox from 2016 18 , and recently in Northern Italy from foxes, badgers, and stone martens between 2018 and 2019 19 . Based on these epizootic events, it can be assumed that this lineage will be present among European wild animals, and detected from wadings for a long time to come and may reappear frequently in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly, the viral infection caused by CDV is associated with respiratory, gastrointestinal, and nervous system disorders in carnivores. Several studies on the clinical and pathological aspects of different kinds of CNS symptoms in dogs have been published over the years (Headley et al 2009;Pratakpiriya et al 2017;Trogu et al 2021). A compilation and summary of the clinical information on canine CNS symptoms has been provided in the articles on this subject.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these proteins play a vital role in determining host range and tropism (Seki et al 2003). Complete H gene sequence studies have found widely distant groups of CDV isolates, although some connections among these lineages remain uncertain (Trogu et al 2021). To our knowledge, the patterns of selection or recombination, as well as their relationship to the many cases of emergence in dogs with neurological symptoms, have not been investigated in any study to our knowledge.…”
Section: Introductionmentioning
confidence: 99%